2021
DOI: 10.12659/msm.930031
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Total Thoracic Endovascular Aortic Repair in Treatment of Kommerell Diverticulum Combined with Right-Sided Aortic Arch

Abstract: Kommerell diverticulum (KD) combined with right-sided aortic arch (RAA) and aberrant left subclavian artery (ALSA) are rare and limited to a few case reports and small series. Thoracic endovascular aortic repair (TEVAR), which is mini-invasive, is widely utilized in complicated aortic disease. We performed a systematic review of the literature to identify all patients who underwent endovascular repair for KD in terms of technical feasibility and procedural outcomes. Published and accepted studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to a systemic review endovascular repair was used to treat both symptomatic and asymptomatic cases with safe and favorable results. Thrombosis and shrinkage of the aneurysm were noted in 71% of patients on follow-up CT scans [13] .…”
Section: Discussionmentioning
confidence: 98%
“…According to a systemic review endovascular repair was used to treat both symptomatic and asymptomatic cases with safe and favorable results. Thrombosis and shrinkage of the aneurysm were noted in 71% of patients on follow-up CT scans [13] .…”
Section: Discussionmentioning
confidence: 98%
“…According to Page et al in 2021 [ 29 ], PRISMA 2020 would not assess the quality of systematic reviews; however, familiarity and guidance by its checklist and instructions are crucial to conducting a systematic review that completely captures all recommended information. The reporting of PRISMA in the submitted systematic review follows suit of recently published systematic reviews that also reported guidance by the PRISMA 2020 guidelines without conducting a meta-analysis [ 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%